FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA ANEMIA PADA IBU HAMIL DI RUMAH BERSALIN PERMATA BUNDA PURWAKARTA - Daris Yolanda Sari (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
Background: According to data of WHO 2005, more than 500,000 women passed away each year. According to Indonesian Health Demographic Survey (SDKI) 2008, Maternal Mortality Rate (AKI) in Indonesia was 228 of 100,000 live births. According to data of the World Health Organization (WHO), 20% of 515,000 deaths around the world is caused by anemia. In Indonesia, according to Household Health Survey (SKRT) 1992, it is reported that 63.5% pregnant women suffer from anemia. Methods: This study was conducted using descriptive design with cross sectional and secondary data obtained in May. Samples of this study were all of 92 total population of pregnant women who procured laboratory examination in Permata Bunda Maternal Hospital Purwakarta . Results: According to bivariate analysis, it is obtained that there is a significant relationship between the incidents of anemia in pregnant women and women’ education with the p value = 0,000, and pregnancy spacing with p value = 0,000. Based on the data analysis, it is obtained that description shows that there is a more significant relationship between predisposition variable and the incidents of anemia on pregnant women with their education by OR of 1,106, on pregnancy spacing of more than two years with no giving birth experience by OR of 1,122. Conclusion: There is a significant relationship between the incidents of anemia in pregnant women and women’ education and pregnancy spacing with p value = 0,000. no giving birth experience by OR of 1,122.